Enhanced electrical conductivity of polymer nanocomposite based on edge-selectively functionalized graphene nanoplatelets - Cho, Jaehyun; Lee, Hyeseong; Nam, Ki-Ho; Yeo, Hyeonuk; Yang, Cheol-Min; Seong, Dong Gi; Lee, Doojin; Kim, Seong Yun (ELSEVIER SCI LTD, 2020)
Achieving high filler dispersion in a polymer composite is very important for effectively and efficiently imparting several advantages of functional fillers to the composite. To this end, we have suggested a synthesis of polyamide 6 via in situ ring-opening polymerization of epsilon-caprolactam and edge-selectively functionalized graphene nanoplatelets without defects on its basal plane synthesized by a ball-mill process with dry ice. As a consequence, the final graphene nanocomposite possesses highly dispersed filler and has enhanced electrical conductivity due to its undistorted sp(2) hybridization after functionalization. This approach is a promising way of incorporating filler into polymer composites, effectively implementing highly electrical conducting graphene without its aggregation and damage to its inherent properties after functionalization.
Keywords: EFFECTIVE THERMAL-CONDUCTIVITY; NONCOVALENT FUNCTIONALIZATION; GAS BARRIER; COMPOSITES; OXIDE; FACILE